Feasibility of a Composite Measure of Pulmonary Vascular Impedance and Application to Patients with Chronic RV Failure Post LVAD Implant - Bachman, Timothy N.; Nouraie, S. M.; Williams, L. E.; Boisen, M. L.; Kim, K.; Borovetz, H. S.; Schaub, R.; Kormos, R. L.; Simon, M. A. (Cardiovascular engineering and technology, 2024)
Pulmonary vascular impedance (PVZ) describes RV afterload in the frequency domain and has not been studied extensively in LVAD patients. We sought to determine (1) feasibility of calculating a composite (c)PVZ using standard of care (SoC), asynchronous, pulmonary artery pressure (PAP) and flow (PAQ) waveforms; and (2) if chronic right ventricular failure (RVF) post-LVAD implant was associated with changes in perioperative cPVZ. PAP and PAQ were obtained via SoC procedures at three landmarks: T(1), Retrospectively, pre-operative with patient conscious; and T(2) and T(3), prospectively with patient anesthetized, and either pre-sternotomy or chest open with LVAD, respectively. Additional PAP’s were taken at T(4), following chest closure; and T(5), 4–24 h post chest closure. Harmonics (z) were calculated by Fast Fourier Transform (FFT) with cPVZ(z) = FFT(PAP)/FFT(PAQ). Total pulmonary resistance Z(0); characteristic impedance Zc, mean of cPVZ(2–4); and vascular stiffness PVS, sum of cPVZ(1,2), were compared at T(1,2,3) between +/-RVF groups. Out of 51 patients, nine experienced RVF. Standard hemodynamics and changes in cPVZ-derived parameters were not significant between groups at any T. In conclusion, cPVZ calculated from SoC measures is possible. Although data that could be obtained were limited it suggests no difference in RV afterload for RVF patients post-implant. If confirmed in larger studies, focus should be placed on cardiac function in these subjects.